Neural network applications in control - Irwin, G. W. 1950- (George William); Warwick, Kevin 1954-; Hunt, K. J. 1963- (Kenneth J.) (Institution of Electrical Engineers, 1995)
The book comprises 12 chapters dealing with the following subjects: digital neural networks; neurocontrol; approximation theory; electric power and chemical process applications; dynamic artificial neural network; nonlinear process control; speech, vision and colour applications; real-time drive control; fuzzy-neural control in intensive-care blood pressure management; system identification; neurofuzzy adaptive modelling; and nonlinear dynamical process.